MANAJEMEN INKLUSIF DENGAN PRINSIP MAQASHID AL SYARI‘AH DALAM PENGHITUNGAN ZAKAT DAN PAJAK - Musnandar, Aries (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
This article describes the condition of applying zakah and tax calculation management in Indonesia. The enactment of tax regulation is to get the government to obtain the maximum national income to be utilized for social welfare.In fact, zakah as a potential economic instrument inincreasing the national income, has been paid less attention by the government rather than the issue of tax payment. Although the government has issued regulations on the integration of zakah and tax calculations, some weaknesses found especially related to the implementation of the zakah and tax calculation. This paper concludes that the governement is expected to implement and inclusive management based on principle of maqashid al syari‘ah in determining the amount of zakah and tax for better collection and distribution of zakah and tax. The principle of maqashid al syari‘ah means that Islamic law has a purpose to prosper the people. Similarly, zakat together with taxes essentially aims at alleviating poverty and improving the welfare of Muslims.